THE STUDY OF THE DEPENDENCE OF THE FLUX LINKAGE OF THE UNIT PERMANENT MAGNETS WITH THE COIL FROM THE LENGTH OF THE LAST - Novykov, V. F.; Burilov, S. V.; Voskoboinik, V. E.; Dzenzerskyi, V. O. (Science and Transport Progress, 2006)
A research of the effect of coil length on the Fourier coefficients of decomposition of dependence of interlinkаge of the block of permanent magnets with the track structure coil on their mutual position is conducted. As a result of the research the dependence of Fourier coefficients on the coil length has been established, which allows to simplify optimization of design of a linear synchronous motor with excitation from a block of permanent magnets.